A meta-analysis of the platelet-lymphocyte ratio: A notable prognostic factor in renal cell carcinoma. Issue 2 (June 2022) - Zhou, Xiao; Luo, Guangcheng
The platelet-lymphocyte ratio (PLR) has been assessed in some studies on renal cell carcinoma (RCC), but the results have been inconsistent. This meta-analysis aims to review and report the latest data regarding the prognostic role of the PLR in RCC patients. Articles were searched in the PubMed, EMBASE, and Cochrane Library electronic databases. Studies were filtered according to a selection strategy, and data corresponding to the index of interest were extracted. A fixed-effects model or random-effects model was selected based on heterogeneity. The sensitivity analysis was carried out by eliminating the studies one by one. Finally, funnel plots and Egger's test were used to assess publication bias, and the trim and fill method was used to assess the impact of bias on the results. In total, 15, 193 patients with RCC from 44 studies were included in this meta-analysis. The pooled analysis indicated that the higher the PLR was, the poorer the prognosis for RCC patients in terms of overall survival (hazard ratio (HR) = 1.01 (95% confidence interval (CI) 1.00, 1.02), P  = 0.010), cancer-special survival (CSS) (HR = 1.21 (95% CI 1.00, 1.46), P  = 0.05), progression-free survival (HR = 1.44 (95% CI 1.28, 1.62), P < 0.00001), recurrence-free survival (HR = 1.73 (95% CI 1.11, 2.71), P  = 0.02), disease-free survival (HR = 1.63 (95% CI 0.91, 2.94), P  = 0.01) and metastasis-free survival (HR = 1.223 (95% CI 0.712, 2.099), P  = 0.466). In the subgroup analysis of high PLR, targeted treatment, TKI use, nivolumab use, surgical treatment, clear cell RCC, metastasis, Asian race, and high PLR were related to poor prognosis. This study showed that a high PLR was associated with the poor prognosis of RCC patients, but more studies are needed to confirm the value of the PLR.